B R AMBEDKAR : PERSPECTIVES ON SOCIAL EXCLUSION AND INCLUSIVE POLICIES - SUKHADEO THORAT; NARENDER KUMAR (NEW DELHI OXFORD UNIVERSITY PRESS, 2009)
The contribution of social activist and thinker Ambedkar in the development of inclusive policies during the British rule and its culmination into the reservation policy in the Constituent Assembly is immense. In this volume, original documents, memorandums, and writings by Ambedkar are put together to highlight the process of development in these policies and his thinking.
Keywords: B R AMBEDKAR; PEOPLE WITH SOCIAL DISIBILITIES - GOVERNMENT POLICY